2022
DOI: 10.1155/2022/7976319
|View full text |Cite
|
Sign up to set email alerts
|

A Channel State Information-Based Key Generation Scheme for Internet of Things

Abstract: Internet-of-Things (IoT) networks generally contain resource-constrained devices that require an energy-efficient key generation procedure to producing secure keys at a faster rate. The physical characteristics of the wireless channel can be exploited to secure communication within IoT networks. In particular, secret keys can be generated by leveraging on the randomness of the wireless physical channel between two communicating parties. The conventional mechanism of generating keys at the physical layer, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This proposed technique combines with a special guard band scheme to achieve a better secret key disagreement ratio performance. In [13], the authors suggested extracting the secret key for Internet-of-Things (IoT) devices in a static environment. In this method, both the channel phase and amplitude are utilized in the key generation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This proposed technique combines with a special guard band scheme to achieve a better secret key disagreement ratio performance. In [13], the authors suggested extracting the secret key for Internet-of-Things (IoT) devices in a static environment. In this method, both the channel phase and amplitude are utilized in the key generation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The unique properties of wireless channels, such as their time-varying, short-term reciprocity, and space-time uniqueness within the coherence interval T c , provide a natural source for generating secret keys [7]. The key-generation process involves channel probing, measurement quantization, information reconciliation, and privacy amplification, resulting in the establishment of a secure shared key between the sender and receiver [8]. The secret key capacity is a crucial aspect of this field of study.…”
Section: Introductionmentioning
confidence: 99%